Family Ownership Plan in the Municipality of Tandil: space of appropriations and contradictions between 1993 and 2016 (Huellas, 2020)
From the 1990s onwards, the Family Ownership Plan is launched in the Municipality of Tandil, favoring the generation of urban land for low-income families. This article aims to achieve an approach to the implementation of the plan, in order to analyze its development and consolidation throughout the period under study, from 1993 to 2016. The families, the State and the market contribute to the configuration of the plan and appropriate it under the logic that distinguishes each of the actors. The data obtained, which was based on written documentation and semi-structured interviews, was systematized. The results show that the State legitimizes some of the family practices that are considered informal or that do not follow the guidelines established by the plan, either through concrete action or due to lack of decision-making, and point out that the market influences this process.
Keywords: urban land; appropriation; Family Ownership Plan